2010
DOI: 10.1038/sj.ebd.6400734
|View full text |Cite
|
Sign up to set email alerts
|

Treating periodontal disease may improve metabolic control in diabetics

Abstract: There is some evidence of improvement in metabolic control in people with diabetes, after treating periodontal disease. There are few studies available and individually these lacked the power to detect a significant effect. Most of the participants in the study had poorly controlled type 2 DM and there was little data from randomised trials on the effects on people with type 1 DM. Improving periodontal health is an important objective in itself. However, in order to understand the potential of this treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
0
13
0
3
Order By: Relevance
“…Oral health status has long been reported as an important determinant of morbidity and mortality in the general population (1,15,20,33,39,51,62,63,68,72,78,88,91,101,102,106,108). An eminent component of oral health is the number of remaining teeth, with tooth loss resulting in partial or complete edentulism as its consequence.…”
mentioning
confidence: 99%
“…Oral health status has long been reported as an important determinant of morbidity and mortality in the general population (1,15,20,33,39,51,62,63,68,72,78,88,91,101,102,106,108). An eminent component of oral health is the number of remaining teeth, with tooth loss resulting in partial or complete edentulism as its consequence.…”
mentioning
confidence: 99%
“…Local inflammation in patients with diabetes promotes a rise in blood glucose, worsening the metabolic state (Bender & Bender 2003), much like periodontal disease (Katz 2001). It suggests that when periodontal and periapical infections are treated, it may improve diabetic treatment aiming to support metabolic disease control (Rees 2000, Simpson et al 2010, Vergnes 2010. When untreated, these infections may foment metabolic alterations caused by increased overall insulin resistance promoted by the activation of inflammatory pathways (Segura-Egea et al 2012).…”
Section: Dm and Inflammatory Pulpal And Periapical Diseasementioning
confidence: 99%
“…One prospective 5 year study of 2,973 nondiabetic individuals demonstrated that those with severe periodontitis had approximately a 5x greater absolute increase in HbA1c over the observation period when compared to nonperiodontitis patients. Also, some reviews and meta-analyses have identified reductions in HbA1c following periodontal therapy [14,15].…”
Section: Risk Factors Of Periodontitismentioning
confidence: 99%